RISK ANALYSIS ON THE CONSTRUCTION PROJECT OF THE SOUTH KALIMANTAN REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) BUILDING - Ramadaayanti, Herni; Yuliana, Candra (Universitas Lambung Mangkurat, 2025)
In its implementation, construction projects are often faced with various risks that can hinder the achievement of goals. Likewise, the construction project of the South Kalimantan House of Representatives (DPRD) Building which is planned to consist of three main floors and a basement will certainly face its own challenges in the project, such as extreme weather, or even delays in material delivery, can be the main cause of risks or obstacles in the project.In this project, data was obtained from questionnaires and interviews with the project party and competent parties outside the project. The risk analysis in this project uses the Severity Index method and the Probability and Impact Matrix method. Furthermore, the dominant risk mitigation is by conducting interviews with competent project parties.The results of the research from the risk analysis in this project obtained 26 risk variables consisting of the Undesirable and Unacceptable categories, risk responses were obtained by means of Risk Reduction for 22 risk variables, Risk Avoidance for 3 risk variables, Risk retention for 1 risk variable Keywords: Analisis risiko, Severity Indeks, Probability and Impact Matrix